Internet of Things (IoT) Integration for Real-Time Monitoring in Smart Cities - T. Irfan Fajri; Novi Rahayu; Wasiran; Yusuf Unggul Budiman; Novrini Hasti (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2025)
The advancement of Internet of Things (IoT) technology has opened great opportunities for the implementation of real-time monitoring systems in supporting smart city management. This research aims to develop an IoT integration model that can monitor various urban aspects, such as traffic management, energy consumption, waste management, and air quality, in an efficient and integrated manner. The model is designed to collect, process, and analyze data from various IoT sensors scattered in urban areas, with a focus on delivering information in an integrated manner. urban areas, with a focus on delivering real-time information to the government and the public. The research methodology includes the development of development of an IoT-based system prototype that integrates hardware and hardware and software with the support of cloud computing architecture for data management. data management.